Hubungan Keteraturan Minum Obat terhadap Pengendalian Tekanan Darah pada Pasien Hipertensi di Wilayah Kerja Puskesmas Raya Pematangsiantar - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Sinaga, Fransius P. (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
Hypertension is a chronic condition that requires long-term management due to its strong association with an increased risk of serious complications when blood pressure is not adequately controlled. One of the key factors influencing the success of hypertension management is patient adherence to antihypertensive medication. However, suboptimal adherence remains a common problem and may lead to poor therapeutic outcomes. This literature review aimed to examine the relationship between adherence to antihypertensive medication and blood pressure control among patients with hypertension. A systematic search of the literature was conducted using the PubMed and Google Scholar databases with relevant keywords combined through Boolean operators. The selected articles were screened based on predefined inclusion and exclusion criteria, including original research articles published within the last ten years, accessible in full text, and addressing the association between medication adherence and blood pressure in hypertensive patients. The findings of the reviewed studies indicate that most articles reported a significant relationship between medication adherence and blood pressure levels. Patients with higher adherence to antihypertensive therapy tended to achieve better blood pressure control compared to those with lower adherence. Although variations in the strength of the reported associations were observed across studies, the overall direction of the relationship was consistent. These results suggest that adherence to antihypertensive medication plays an essential role in achieving optimal blood pressure control. Therefore, this review highlights the importance of continuous efforts to improve patient adherence as part of effective hypertension management strategies aimed at reducing the risk of long-term complications.